Experimental investigation on mahua methyl ester blended with diesel fuel in a compression ignition diesel engine. Issue 3 (3rd April 2019) - Vijay Kumar, M.; Veeresh Babu, A.; Ravi Kumar, P.
Abstract : In this article, the mahua tree's high importance in the present-day plantations is described and the preparation of mahua methyl ester (MME) from the raw mahua seed oil by the two methods of the transesterification process is described. The tested physical properties were compared with the requirement of ASTM D-6751. The obtained MME and its blends of B20, B40, B60, and B80 were investigated in an unmodified diesel engine. From the results of the performance, it has been observed that brake-specific fuel consumption and brake thermal efficiency are slightly improved (B20 and B40) at part-load conditions and approach diesel at full-load conditions. From combustion analysis, it was seen that ignition delay was shorter for biodiesel and its blends compared with the diesel fuel. The emission characteristics of carbon monoxide, hydrocarbons, and smoke opacity were reduced for all the fuel blends, but at high temperatures they undergo an endothermic reaction and produced various oxides of nitrogen.